PENDUGAAN DAERAH PENANGKAPAN IKAN TENGGIRI BERDASARKAN DISTRIBUSI SUHU PERMUKAAN LAUT DAN KLOROFIL-a DI PERAIRAN BANGKA - Bukhari Bukhari; Wahyu Adi; Kurniawan Kurniawan (Fakultas Perikanan dan Ilmu Kelautan UNDIP, 2017)
Fishing activity definitely influenced by the condition of fishing ground. Therefore, the information about potential fishing ground is needed by fisherman in the fishing activity. Chlorophyll-a is the primary productivity in the waters. Chlorophyll-a development of the waters affected by sea surface temperature (SST). The purpose of this study are to map the distribution of chlorophyll-a and SST in the Bangka waters and to predict fishing areas in the Bangka waters. Fishing grounds were estimated using three indicators namely the concentration of chlorophyll-a, SST and catch per unit effort (CPUE). Distribution of chlorophyll-a and SST in the waters of Bangka using Aqua MODIS image data. Distribution of the average value of the highest SST in the waters of Bangka occur in first transitional season that is equal 31,2˚C, while the lowest value occurred in the western season namely 28,1˚C. The concentration of chlorophyll-a in the west tend to be high season with an average value of 1,3 mg/m3, while in the transitional season 1 the value of chlorophyll-a concentration lower at 0,4 mg/m3. Most of the catch obtained in the first transitional season 470.306 kg with a value of CPUE 1.256,44 kg/trip. Lowest number of catches on the west season is 218.753 kg with a value of CPUE 551,11 kg/trip. The Results from in situ data retrieval of chlorophyll-a concentration values were highest at station 5 at 1,602 mg/m3, while the lowest concentrations of chlorophyll-a occurred at station 2 of 0,801 mg/m3. While sea surface temperatures in the study area ranged between 29°C to 31°C. The relationship between oceanographic factors may determine the potential fishing area. Based on the analysis of chlorophyll-a and SST, the waters of Bangka viable as a predictor of potential mackerel fishing area. The spread of fishing areas not just in the waters close to fishing base (PPN Sungailiat), but also in waters far enough away from the fishing base that includes locations around Karang Sembilan, Karang Tinggi, Karang Bahaya, Toti Island and the Tujuh Island.